Gene expression profile of PM014 of immortalized mouse lung epithelial cells in response to the effect of PM014 on radiation-induced fibrosis - Shin, Dasom; Joo, Kyung Goo; Kang, Mi Jung; Pak, Sehyun; Kim, Youn-Sub; Bae, Hyunsu (Advances in traditional medicine (Online), 2019)
Radiotherapy is a major method for cancer treatment, but it frequently causes various side effects such as radiation-induced pneumonia and pulmonary fibrosis. Drugs to treat these side effects are urgently needed in the clinic, since there is no clearly defined medication for treating these symptoms. Previous studies demonstrated that the herbal formula, PM014, is effective for radiation-induced lung injury and fibrosis in mice. In this study, we investigated gene expression profiles to understand the mechanism of action behind the effects of PM014 on radiation induced damage in immortalized lung epithelial cells, MLE12. We performed QuantSeq 3′ mRNA-Seq analysis on the mRNA from radiation treated MLE-12 cells in the presence and absence of PM014. Transcriptome analysis found that 217 genes were significantly affected by PM014. Among them (217 genes, > twofold, p value < 0.05, 4 normalize), 77 genes were found to be upregulated, and 140 genes were downregulated in response to PM014 treatment in a dose dependent manner. Using the Kyoto Encyclopedia of Genes and Genomes analysis, we found that genes involved in cytokine–cytokine receptor interaction pathways were the most strongly affected by PM014. Based on these data, we selected 20 genes, and performed real-time PCR. Expression of 11 genes, including IL - 18 , IL - 12a , Tnfrsf9 , IL - 17 , CCR5 , Blnk , Irf8 , Nrros , TGF - β , Relt , and Cxcl2 was increased after irradiation, while PM014 treatment showed the reversed expression pattern of these genes. Therefore, PM014 may be useful for the treatment of radiation induced lung injury by modulating genes involved in cytokine–cytokine receptor interaction pathway.